ON QUASI-MINIMAL ISOMETRIC IMMERSIONS INTO NON-FLAT SEMI RIEMANNIAN SPACE FORMS OF INDEX TWO - Turgay, Nurettin Cenk; Kelleci, Alev; Sen, Ruya Yegin; Canfes, Elif Ozkara (Inst Biophysics & Biomedical Engineering Bulgarian Acad Sciences, 2019)
In this paper, first we gave a summary of recent results on biconservative immersions. Then, we obtained a necessary and sufficient condition for the existence of biconservative quasi-minimal immersions into a four dimensional semi-Riemannian space form of index two with non-zero sectional curvatures. We also constructed an explicit example of biconservative quasi-minimal surface.
20th International Conference on Geometry, Integrability and Quantization -- JUN 02-07, 2018 -- Varna, BULGARIA
Keywords: Biconservative immersions; biharmonic submanifolds; Lorentzian surfaces; quasi-minimal surfaces; semi-Riemannian space-forms